2019
DOI: 10.3892/etm.2019.8275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of aspirin combined with clopidogrel in treating cerebral infarction and its effect on serum hs-CRP, sICAM-1 and TNF-α

Abstract: Clinical efficacy of aspirin combined with clopidogrel in treating cerebral infarction and its influence on serum high-sensitivity C-reactive protein (hs-CRP), soluble intercellular adhesion molecule-1 (sICAM-1) and tumor necrosis factor-α (TNF-α) were explored. Ninety patients with acute cerebral infarction treated in Yidu Central Hospital of Weifang were analyzed, and those treated with aspirin alone were group A (n=40) and those treated with aspirin and clopidogrel were group B (n=50) according to the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…CSVD is an intracranial small vessel lesion in sites such as arterioles, small veins, and capillaries caused by a combination of factors, which damages the white matter and gray matter in depth of brain and finally leads to a series of pathological and neuroimaging changes, thereby resulting in cognitive impairment and other clinical syndromes in patients [13]. Studies have confirmed [14] that CSVD is not only related to vascular cognitive dysfunction but also to the pathogenesis of neurodegenerative diseases such as Alzheimer's disease (AD), and as these two diseases are overlapped to some extent, most AD patients have signs of CSVD, including cognitive dementia, progressive cognitive decline, bladder sphincter dysfunction, and mental disorders [15]. Currently, there is no consensus on CSVD pathogenesis, but it may be due to the fact that chronic progressive subclinical ischemia in the brain increases vascular permeability, causing extravasation of intravascular substances, disruption of the blood-brain barrier, local inflammatory response, and then resulting in vascular and perivascular tissue damage [16].…”
Section: Discussionmentioning
confidence: 99%
“…CSVD is an intracranial small vessel lesion in sites such as arterioles, small veins, and capillaries caused by a combination of factors, which damages the white matter and gray matter in depth of brain and finally leads to a series of pathological and neuroimaging changes, thereby resulting in cognitive impairment and other clinical syndromes in patients [13]. Studies have confirmed [14] that CSVD is not only related to vascular cognitive dysfunction but also to the pathogenesis of neurodegenerative diseases such as Alzheimer's disease (AD), and as these two diseases are overlapped to some extent, most AD patients have signs of CSVD, including cognitive dementia, progressive cognitive decline, bladder sphincter dysfunction, and mental disorders [15]. Currently, there is no consensus on CSVD pathogenesis, but it may be due to the fact that chronic progressive subclinical ischemia in the brain increases vascular permeability, causing extravasation of intravascular substances, disruption of the blood-brain barrier, local inflammatory response, and then resulting in vascular and perivascular tissue damage [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fukuuchi et al [8] thought that clopidogrel was the first choice for treating noncardiac embolic cerebral infarction. Li et al [9] proposed that clopidogrel could improve the efficacy of aspirin in the treatment of ACI. Cerebral ischemia induces an increase in free radicals, which brings about ischemic brain damage such as edema and neuropathy [10].…”
Section: Introductionmentioning
confidence: 99%
“…A study has verified that inflammatory response is one of the important pathophysiological mechanisms of acute ischemic stroke, 22 and TNF-α, IL-6, and hs-CRP are important inflammatory mediators of secondary brain injuries in patients with acute ischemic stroke. This study analyzed the serum levels of inflammatory factors before and after treatment.…”
Section: Discussionmentioning
confidence: 97%